Technology and Architecture Analyzing Architecture from a Technological Standpoint (Journal of Engineering, 2024)
This research is concerned with defining specific analytical terms that could be used in observing the architectural product from a technological view point. This was achieved by founding an inclusive analytical structure for architectural technology based on the view of technology philosopher Carl Mitcham, who states that technology, at a given time and place, could be observed through its four manifestations: Objects, Process, Knowledge and Volition. The research has showed that these manifestations  define architectural technology as the actual context within which relations between components of these manifestations emerge, get organized and change. Five analytical terms have been induced: materials and their processing, structure and its relations,detail building, tectonic values and formal expression. These are introduced as terms affecting the formulation of architectural product, and thus can be used for analyzing it technologically.